Морфологический анализ фонокардиосигнала - Гвоздецкая, А. В.; Жемчужкина, Т. В.; Носова, Т. В. (ХНУРЕ, 2019)
The auscultation of the heart is still the first basic analysis tool used to evaluate the functional state of the heart, as well as the first indicator used to submit the patient to a cardiologist. In order to improve the diagnosis capabilities of auscultation, signal processing algorithms are currently being developed to assist the physician at primary care centers for adult and pediatric population. A basic task for the diagnosis from the phonocardiogram is to detect the events (main and additional sounds, murmurs and clicks) present in the cardiac cycle.
Keywords: фонокардиосигнал; анализ морфологический; система сердечно-сосудистая; коэффициент кореляции